PENEMUAN HUKUM KONSEPSI DPD RI SEBAGAI LEMBAGA PERWAKILAN DAERAH - Ardianto, Andri (Jurnal Yuridis, 2020)
The Regional Representative Council of the Republic of Indonesia (DPD RI) is a state institution that was born from the 1945 NRI Amendment process. The formation of the DPD RI was meant not only to reform the parliamentary structure into two chambers, the formation of the DPD RI was a constitutional effort intended to better accommodate regional votes by giving channels, as well as roles for the regions. In that perspective, the DPD RI must play a more important role in bridging local regional aspirations with national development policies. Thus, regional interests and aspirations can be integrated and aligned with national policies. If the DPR brings political aspirations of the people, then the DPD should carry regional aspirations that are not only political in nature but have social and cultural values in accordance with the variety of regions it represents. In essence, the role of the DPD is more emphasized on the importance of accommodating and aggregating the aspirations and interests of the regions to balance the hegemony of the DPR which carries the aspirations of the people which are only political. This research will focus on the extent to which the DPD RI has carried out its role as mandated and the ideals of its formation as regional representatives. Whether the presence of the DPD has accommodated and aggregated regional interests and has also been able to avoid legislative power being only concentrated in one institution (check and balance).